2015
DOI: 10.1021/acs.jproteome.5b00536
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Search Engines and Postprocessing Approaches to Maximize Peptide and Protein Identification for High-Resolution Mass Data

Abstract: The two key steps for analyzing proteomic data generated by high-resolution MS are database searching and postprocessing. While the two steps are interrelated, studies on their combinatory effects and the optimization of these procedures have not been adequately conducted. Here, we investigated the performance of three popular search engines (SEQUEST, Mascot, and MS Amanda) in conjunction with five filtering approaches, including respective score-based filtering, a group-based approach, local false discovery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…We also evaluated 0.35 Da tolerance for fragment ion masses analyzed by HCD-IT as suggested by previous reports[ 27 ]. Lower peptide/protein identifications were achieved relative to the use of 1.0 Da tolerance when using SEQUEST-PeptideProphet as shown in S1D Fig and no difference was observed when using SEQUEST-Percolator as we previously studied [ 28 ]. Thus, 1.0 Da tolerance for fragment ion masses analyzed by ion trap was applied in this study as we previously reported[ 28 ].…”
Section: Methodsmentioning
confidence: 83%
“…We also evaluated 0.35 Da tolerance for fragment ion masses analyzed by HCD-IT as suggested by previous reports[ 27 ]. Lower peptide/protein identifications were achieved relative to the use of 1.0 Da tolerance when using SEQUEST-PeptideProphet as shown in S1D Fig and no difference was observed when using SEQUEST-Percolator as we previously studied [ 28 ]. Thus, 1.0 Da tolerance for fragment ion masses analyzed by ion trap was applied in this study as we previously reported[ 28 ].…”
Section: Methodsmentioning
confidence: 83%
“…However, this flaw can be overcome when combined with the followed quality control methods by considering the distributions of target and decoy hits and reanalyzing the original scores. The SVM-based percolator algorithm has been proved to be an ideal QC method [ 11 , 29 ]. Thus, we further analyzed Mascot’s results by PepDistiller [ 11 ] (a bulit-in Percolator classifier), X!Tandem’s results and MS-GF+’s results by Percolator [ 27 , 30 ], Tide’s results and Comet’s results by Percolator intergrated in Crux [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…MS Amanda places an emphasis on high-accuracy MS2 data and is therefore optimized for high resolution and mass accuracy at both the MS1 and MS2 levels. 24 As the MS2 resolution increased from 30,000 to 60,000 fewer peptides were identified (40, 29, 26, respectively) (see Figure 1C). The average top score of the peptides did not significantly increase as the resolution increased (see Figure 1D).…”
Section: Identification Of Histone Ptms Using Dda Methodsmentioning
confidence: 97%
“…In addition to processing the data with Mascot, an alternative search engine, MS Amanda, was also used. MS Amanda places an emphasis on high‐accuracy MS2 data and is therefore optimized for high resolution and mass accuracy at both the MS1 and MS2 levels . As the MS2 resolution increased from 30,000 to 60,000 fewer peptides were identified (40, 29, 26, respectively) (see Figure C).…”
Section: Data‐acquisition Methodsmentioning
confidence: 99%